2012
DOI: 10.1242/dev.071696
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages are crucial for epithelial cell death and adipocyte repopulation during mammary gland involution

Abstract: SUMMARYMammary gland development is dependent on macrophages, as demonstrated by their requirement during the expansion phases of puberty and pregnancy. Equally dramatic tissue restructuring occurs following lactation, when the gland regresses to a state that histologically resembles pre-pregnancy through massive programmed epithelial cell death and stromal repopulation. Postpartum involution is characterized by wound healing-like events, including an influx of macrophages with M2 characteristics. Macrophage l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
120
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 44 publications
3
120
0
1
Order By: Relevance
“…Therefore, the loss of ZnT2 in adipocytes may mirror insulinlike effects on lipogenesis that stunt ductal growth (60) or may affect the synthesis or release of paracrine factors, such as adiponectin and collagen VI (61) from adipocytes that initiate epithelial/mesenchymal interaction and facilitate ductal expansion (55). Finally, macrophages are also important for mammary gland development, as they are recruited to the epithelial cells to support proliferation for ductal outgrowth (30,62) by supplying growth factors, cytokines, and chemokines (63) or by engulfing apoptotic cells that interfere with epithelial proliferation (64). The lack of cell proliferation in ZnT2-null mice suggests that loss of ZnT2 in macrophages may not be able to support normal epithelial and fibroblast proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the loss of ZnT2 in adipocytes may mirror insulinlike effects on lipogenesis that stunt ductal growth (60) or may affect the synthesis or release of paracrine factors, such as adiponectin and collagen VI (61) from adipocytes that initiate epithelial/mesenchymal interaction and facilitate ductal expansion (55). Finally, macrophages are also important for mammary gland development, as they are recruited to the epithelial cells to support proliferation for ductal outgrowth (30,62) by supplying growth factors, cytokines, and chemokines (63) or by engulfing apoptotic cells that interfere with epithelial proliferation (64). The lack of cell proliferation in ZnT2-null mice suggests that loss of ZnT2 in macrophages may not be able to support normal epithelial and fibroblast proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages from MAFIA mice express a modified Fas receptor that, in response to a dimerization-inducing small molecule (AP20187), triggers Fas-mediated apoptosis. Depletion of macrophages immediately prior to weaning impaired apoptosis within the secretory mammary epithelium, despite milk stasis and STAT3 activation [105]. These results demonstrate that macrophages are necessary to initiate apoptosis in the mammary epithelium.…”
Section: Stromal-epithelial Interactionsmentioning
confidence: 69%
“…Reduction in M2 Macrophage Recruitment in Mammary Gland Involution in Nucling-KO Mice-Macrophages with an alternatively activated M2 phenotype have been shown to play a role in involution (14). We also previously reported that Nucling affected the number of Kupffer cells in the liver (22).…”
Section: Overexpression Of Nucling During Mammary Gland Involution-bementioning
confidence: 87%
“…Therefore, we attempted to elucidate the contribution of Nucling to M2 macrophage recruitment during mammary gland involution. To achieve this, we examined the expression of Arginase-1 and Ym1, markers of M2 macrophages (14,27). At 36 h of involution, protein levels of Arginase-1 were similar in WT and Nucling-KO mice.…”
Section: Overexpression Of Nucling During Mammary Gland Involution-bementioning
confidence: 99%
See 1 more Smart Citation